Struktur Modal pada Perusahaan Minyak Bumi dan Gas Alam - Subhan Saleh, Dean; Hendriani, Maria; Yuliana Sompi , Maretha (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This research aims to analyze the influence of Profitability, Working Capital Turn Over (WCTO) and Firm Size on Capital Structure with World Oil Prices as a Moderating Variable in Petroleum and Natural Gas Companies listed on the Indonesia Stock Exchange in 2019 - 2023. The population of this research was 29 companies, using purposive sampling techniques to obtain a research sample of 13 companies and observation data of 65 companies. This research is a quantitative research using panel data regression analysis methods and Moderated Regression Analysis using Eviews 13. The partial research results show that Profitability has a significant negative effect on Capital Structure, Working Capital Turn Over (WCTO) and Company Size has a significant positive effect on Capital Structure and World Oil Prices have no effect on Capital Structure. Simultaneous Profit, Working Capital Turn Over (WCTO) and Firm Size together have an influence on Capital Structure. Apart from that, World Oil Prices weaken the influence of Profitability and Working Capital Turnover (WCTO) on Capital Structure and strengthen the influence of Firm Size on Capital Structure.